Intact NKG2D-Independent Function of NK Cells Chronically Stimulated with the NKG2D Ligand Rae-1 - Champsaur, Marine (2010)
Human tumors frequently express membrane-bound or soluble NK group 2, member D (NKG2D) ligands. This results in chronic engagement of NKG2D on the surfaces of NK and CD8(+) T cells and rapid internalization of the receptor. Although it is well appreciated that this phenomenon impairs NKG2D-dependent function, careful analysis of NKG2D-independent functions in cells chronically stimulated through NKG2D is lacking. Using a mouse model of chronic NKG2D ligand expression, we show that constant exposure to NKG2D ligands does not functionally impair NK cells and CD8(+) T cells in the context of viral infection.